Reliability of modified hertels exophthalmometer as an intraoperative tool for assessment of relative globe position in orbital/zygomatic fracture - Abinaya Subramanian; K Santhosh Kumar; G V V. Giri; C Ravindran; Emmanuel Azariah; Madhumita Ramakrishnan (Wolters Kluwer Medknow Publications, 2021)
Introduction: Axial globe position assessment is commonly carried out with Hertels Exophthalmometer. Hertels requires an intact lateral orbital rim for its placement, which is often fractured in zygomatic fractures. Hence, to overcome this problem, we have modified the instrument for its application in zygomatic/orbital fractures. Reliability of this Modified Hertels Exopthalmometer has been already validated in normal healthy patients. Therefore, the aim of this study is to assess the efficacy of the Modified Hertels Exophthalmometer in pateints with zygomatic/orbital fracture. Materials and Methods: This is a prospective study carried out between April 2015 and October 2017, including 20 patients with a mean age of 34 years. Enophthalmos was measured using Modified Hertels in patients with unilateral orbital/zygomatic fracture indicated for surgical intervention by a single observer. The data was collected and statistically analyzed. Paired sample t-test was done to compare the preoperative exophthalmometer reading with readings at different time points. Results: A statistically significant difference was noted (P = 0.031) among the variables of Modified Hertels. We believe this instrument to be of practical use in the assessment of enophthalmos/exophthalmos in patients with lateral orbital trauma, surgery or disease and also precludes the use of rim-based exophthalmometry and other modifications of same.